Research of qualitaty indicators of non-evolvent gears - Tretyak, T. E.; Gutsalenko, Yu. G.; Mironenko, A. L.; Mironenko, S. A. (Public Organization Foundation for Economic Initiatives, Budapest, Hungary, 2020)
The article describes the method of obtaining the mating surfaces of the teeth of non-involute gears as envelopes of the specified surfaces of the teeth of the tools. A scheme for forming pairs of non-involute gears, from which a gearing can be composed, is proposed. The results of the study of the pressure ratio between the teeth of a gear and the overlap ratio of gears when choosing the shape of the tooth profiles are presented.
Keywords: non-involute gearing; shaping of gears; quality indicators of gearing; mechanical engineering